The Effect of Tuba Root Extract (Derris elliptica) with Different Dosage on Survival Rate and Blood Profiles for Broodstock of Tilapia (Oreochromis niloticus) in a Closed Transport System - Kahan Dwi Supardi; Desrina Desrina; Tristiana Yuniarti (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2022)
Fish transportation activity is one of the important components in providing quality broodstock of tilapia. The study was conducted to determine the effect of extract tuba root on the blood profiles and survival of nile tilapia broodstock (Oreochromis niloticus) and also to determine the optimal dose of extract tuba root to produce the highest survival value of nile tilapia broodsctock. The fish used in this study were broodstock from Kendal, Central Java, with a wight 104±4.96 gram. The research method used was a complete randomized design experimental method (RAL) with 5 treatments and 3 replications. The doses of extract tuba root were A (0 ppm), B (0.05 ppm), C (0.1 ppm), D (0.15 ppm) and E (0.2 ppm). The density of tilapia broodstock in each bag is 10 individuals with a transport time of 10 hours. The parameters measured included length of time to faint, time to recover to consciousness, blood profiles (erythrocytes, leukocytes and hemoglobin), survival rate and water quality. The addition of extract tuba root with different doses did significantly affect (P<0.05) the survival rate and leukocytes of nile tilapia broodstock after transportation, but not significantly on erythrocytes and hemoglobin. The highest SR value was treatment D (0.15 ppm) of 96.67% during transportation.